2019
DOI: 10.5194/hess-23-277-2019
|View full text |Cite
|
Sign up to set email alerts
|

Improving soil moisture and runoff simulations at 3 km over Europe using land surface data assimilation

Abstract: Accurate and reliable hydrologic simulations are important for many applications such as water resources management, future water availability projections and predictions of extreme events. However, the accuracy of water balance estimates is limited by the lack of large-scale observations, model simulation uncertainties and biases related to errors in model structure and uncertain inputs (e.g., hydrologic parameters and atmospheric forcings). The availability of long-term and global remotely sensed soil moistu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 121 publications
(136 reference statements)
1
27
0
Order By: Relevance
“…To generate ensembles of forecast states, we perturbed the precipitation and the soil parameters (sand and clay percentage) by applying log normally distributed multiplicative perturbations (with a mean of 1 and standard deviation of 0.15) to the precipitation field and random noise drawn from spatially uniform distribution (±10%) to the sand and clay content, respectively. In the present study, we only updated the soil moisture state variable and kept the soil texture constant for individual ensemble members throughout our simulations instead of joint state and parameter updates of soil moisture and soil texture in the DA approach as used in our previous study 31 . The ensemble size was set to 20 in our assimilation experiment using similar methodology as used in Naz et al 31 .…”
Section: Datasetmentioning
confidence: 99%
See 3 more Smart Citations
“…To generate ensembles of forecast states, we perturbed the precipitation and the soil parameters (sand and clay percentage) by applying log normally distributed multiplicative perturbations (with a mean of 1 and standard deviation of 0.15) to the precipitation field and random noise drawn from spatially uniform distribution (±10%) to the sand and clay content, respectively. In the present study, we only updated the soil moisture state variable and kept the soil texture constant for individual ensemble members throughout our simulations instead of joint state and parameter updates of soil moisture and soil texture in the DA approach as used in our previous study 31 . The ensemble size was set to 20 in our assimilation experiment using similar methodology as used in Naz et al 31 .…”
Section: Datasetmentioning
confidence: 99%
“…In the present study, we only updated the soil moisture state variable and kept the soil texture constant for individual ensemble members throughout our simulations instead of joint state and parameter updates of soil moisture and soil texture in the DA approach as used in our previous study 31 . The ensemble size was set to 20 in our assimilation experiment using similar methodology as used in Naz et al 31 . Our initial study found slightly improved SM estimates when ensemble size was increased from 12 to 20 31 .…”
Section: Datasetmentioning
confidence: 99%
See 2 more Smart Citations
“…Pre-storm soil moisture conditions partly determine whether precipitation will either in ltrate to deeper soil layers or lead to standing water or overland ow. The accuracy of ( ash) ood forecasting systems greatly bene t if up-to-date information on soil moisture is included (Crow and Ryu, 2009;Brocca et al, 2009Brocca et al, , 2010Tramblay et al, 2010;Sutanudjaja et al, 2014;Naz et al, 2019). In particular, soil moisture information improves the understanding of ood peak heights (Wanders et al, 2014b).…”
Section: Excess Water Issuesmentioning
confidence: 99%